Murder at midnight - Avi, 1937- (New York : Scholastic Press, 2009)
Falsely accused of plotting to overthrow King Claudio, scholarly Mangus the magician, along with his street-smart servant boy, Fabrizio, face deadly consequences unless they can track down the real traitor by the stroke of midnight.
Keywords: Magicians -- Fiction; Orphans -- Fiction; Renaissance -- Italy -- Fiction; Mystery and detective stories